Analisis a factors affecting the development of women entrepreneurship and its effects on sustainable social development in urban areas - Nafiseh VarKianipoor; Seyed Mohammadreza Hoseini; rohalla Samiee; Majid Ashrafi (تحقیقات کاربردی علوم جغرافیایی)
Women play an important role in promoting employment and improving the economic situation of society. Therefore, giving them identity and independence and providing the ground for their active participation in various economic and social affairs, especially entrepreneurial activities in urban areas is a very important factor of this great force. The experts’ demographic features are analyzed. Then the components of entrepreneurship value chain and social sustainable development are sifted out using experts’ opinions (twenty of the best women entrepreneur of Golestan province), Fuzzy Delphi method, and De-fuzzy to find the components of intended variables. Validity and reliability of questionnaires are investigated by Cronbach’s Alpha and normal distribution of components and statistical samples are also analyzed by Kolmogorov-Smirnov and Student’s t-Test. In section one, the prioritization and ranking of dimensions and components of entrepreneurship value chain are addressed (by 198 of women entrepreneur of Golestan province) by using hierarchical analysis process method and Expertchoice software. In section two, to measure the relationships between the developing women’s entrepreneurship according to value chain and the social sustainable development, the Correlational research, the Structural equation for factor analysis test, and Smart pls2 software are used that show a statistical significant. In correlational research not only the relationship between variables are detected but also the type and rate of variables relationship are reachable. The results then are discussed. And the model of developing women’s entrepreneurship according to value chain with the approach of social sustainable development is presented. The model helps adjust the developing women’s entrepreneurship and show the strength and weakness.